BANK HEALTH ANALYSIS AND SUSTAINABILITY REPORT ON CORPORATE VALUE WITH INSTITUTIONAL OWNERSHIP AS MODERATION FOR THE 2017-2020 PERIOD - Virginia Felita Halim; Christiana Fara Dharmastuti (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
This research is motivated by the important role of the Bank in managing finances, namely as a collector of funds from the public that includes the dignity of life of many people, then the bank is an institution that is highly highlighted and its health needs to be monitored as well. The number of samples used were 8 banks listed on the IDX for the 2017-2020 period. This study aims to determine the relationship between risk profile, good corporate governance, profitability, capital, and sustainability reports on the value of the corporate, with institutional ownership as a moderating variable. The results show that the variable credit risk (NPL), liquidity risk (LDR), and sustainability reports have a negative effect on corporate value, while the profitability (ROA) and capital (CAR) variables have a positive effect on corporate value, the good corporate governance (GCG) variable does not. affect the value of the corporate. Institutional ownership variable strengthens the influence of liquidity risk (LDR) on corporate value while the capital variable (CAR) is weakened by institutional ownership variable on corporate value.